Bioactive-enriched feed containing agave fructans and turmeric powder as an alternative to antibiotics in early-laying hens - Balcón Pacheco, Cristina D.; García Munguía, Carlos A.; Ozuna, César; Cardona Herrera, Román; García Munguía, Alberto M.; Franco Robles, Elena (Frontiers in Animal Science, 2025)
The increasing restrictions on antibiotic use in poultry production have prompted the search for natural alternatives that improve health and productivity in laying hens. This study aimed to evaluate the effects of dietary supplementation with agave fructans (PRE), turmeric powder (AOX), and their combination (PA) on productive performance, egg quality, hematological status, and gastrointestinal traits in early-laying hens. A total of 120 Lohman White hens (20 weeks old) were randomly assigned to five dietary treatments: basal control (CON), antibiotics (ATB), agave fructans (PRE), turmeric powder (AOX), and the combination of both additives (PA). Results showed that agave fructans improved internal egg quality, increasing albumen and yolk height and egg weight without altering feed intake or conversion. Both PRE and AOX enhanced immune status, evidenced by a reduced heterophil-to-lymphocyte ratio and modulation of leukocyte populations. Gastrointestinal traits were minimally affected, with only slight variations in crop and cecal pH and duodenal organ weight. In conclusion, PRE supplementation provided the most consistent physiological benefits, supporting its use as a sustainable strategy to improve egg quality and welfare in laying hens while reducing reliance on antibiotics.